Assimilation of socially assistive robots by older adults: an interplay of uses, constraints and outcomes - Zafrani, Oded; Nimrod, Galit; Krakovski, Maya; Kumar, Shikhar; Bar-Haim, Simona; Edan, Yael (Frontiers in Robotics and AI, 2024)
By supporting autonomy, aging in place, and wellbeing in later life, Socially Assistive Robots are expected to help humanity face the challenges posed by the rapid aging of the world’s population. For the successful acceptance and assimilation of SARs by older adults, it is necessary to understand the factors affecting their Quality Evaluations Previous studies examining Human-Robot Interaction in later life indicated that three aspects shape older adults’ overall QEs of robots: uses, constraints, and outcomes. However, studies were usually limited in duration, focused on acceptance rather than assimilation, and typically explored only one aspect of the interaction. In the present study, we examined uses, constraints, and outcomes simultaneously and over a long period. Nineteen community-dwelling older adults aged 75–97 were given a SAR for physical training for 6 weeks. Their experiences were documented via in-depth interviews conducted before and after the study period, short weekly telephone surveys, and reports produced by the robots. Analysis revealed two distinct groups: (A) The ‘Fans’ - participants who enjoyed using the SAR, attributed added value to it, and experienced a successful assimilation process; and (B) The ‘Skeptics’ - participants who did not like it, negatively evaluated its use, and experienced a disappointing assimilation process. Despite the vast differences between the groups, both reported more positive evaluations of SARs at the end of the study than before it began. Overall, the results indicated that the process of SARs’ assimilation is not homogeneous and provided a profound understanding of the factors shaping older adults’ QE of SARs following actual use. Additionally, the findings demonstrated the theoretical and practical usefulness of a holistic approach in researching older SARs users.